Problemas familiares y su incidencia en el rendimiento académico de una adolecente de 14 años de la Parroquia Rural Pimocha del cantón Babahoyo - Zamora Jimenez, Maria Belen (2022)
The student's academic performance is closely related to the family and social environment in which he/she lives. The objective of the case study is to analyze how family problems affect the academic performance of a 14 year old adolescent girl from the rural parish of Pimocha in Babahoyo. For the collection of information, a bibliographic research is carried out and a case study that has been diagnosed and approached with psychotherapeutic treatment that includes cognitive behavioral therapy techniques. On the other hand, the mixed research methodology and the case study, descriptive and psychometric methods are applied. The data collection techniques used for the development of the study are the semi-structured interview, clinical history, clinical observation and psychological batteries such as family functioning test (FF- SIL), adolescent self-descriptive inventory IADA, Beck anxiety inventory and the Levis animal drawing and history test. The results indicate that family problems in the patient's environment affect her academic performance and have repercussions on her mental health. Finally, the family problems experienced by the 14-year-old adolescent have a direct impact on her performance in the school environment, with a decrease in academic performance, and also contribute to triggering psychopathological symptoms in the patient.